Principles, Applications, and Biosafety of Plant Genome Editing Using CRISPR-Cas9 - El-Mounadi, Kaoutar; Morales-Floriano, María Luisa; Garcia-Ruiz, Hernan (Frontiers in Plant Science, 2020)
The terms genome engineering, genome editing and gene editing, refer to modifications insertions, deletions, substitutions) in the genome of a living organism. The most widely used approach to genome editing nowadays is based on Clustered Regularly Interspaced Short Palindromic Repeats and associated protein 9 (CRISPR-Cas9). In prokaryotes, CRISPR-Cas9 is an adaptive immune system that naturally protects cells from DNA virus infections. CRISPR-Cas9 has been modified to create a versatile genome editing technology that has a wide diversity of applications in medicine, agriculture, and basic studies of gene functions. CRISPR-Cas9 has been used in a growing number of monocot and dicot plant species to enhance yield, quality and nutritional value, to introduce or enhance tolerance to biotic and abiotic stress, domestication, and other applications. Although biosafety concerns remain, genome editing is a promising technology with potential to contribute to food production for the benefit Gene editing applications This is a provisional file, not the final typeset article of the growing human population. Here we review the principles, current advances and applications of CRISPR-Cas9-based gene editing in crop improvement. We also address biosafety concerns and show that humans have been exposed to Cas9 protein homologues long before the use of CRISP-Cas9 in genome editing.